Effect of Ultrasonic Treatment Combined with Peracetic Acid Treatment Reduces Decay and Maintains Quality in Loquat Fruit - Chen Ling; Jia Xu; Shuang Shao; Li Wang; Peng Jin; Yonghua Zheng (Journal of Food Quality)
The effects of ultrasonic treatment (UT, 400 watts for 6 min) combined with peracetic acid (PA, 0.4% (W/W)) treatment on fruit decay, browning, and quality and physiological changes in loquat fruit stored at 20°C were investigated. The results showed that treatment with UT or PA alone significantly reduced both decay and browning index in loquat fruit compared with the control. The combined treatment was more effective in decreasing decay and browning index and maintaining higher quality parameters than UT or PA treatment alone. Loquat fruits treated with the combined treatment maintained higher activities of polyphenol oxidase (PPO) and peroxidase (POD) than those treated with other treatments. In addition, UT combined with PA treatment significantly reduced the increase of firmness and increased fruit extractable juice, total soluble solid (TSS), and ascorbic acid content in loquat fruit. Moreover, the contents of total phenolics and total flavonoids were enhanced by the combination of UT and PA treatment. The combination of UT and PA treatment could be a useful method to reduce decay and browning in loquat fruit stored at room temperature, which has potential for application in the loquat industry.